(untitled) (International Journal of Communication Systems and Network Technologies, 2013)
In cloud computing, prototype is emerged as an energy efficient approach that facilitates ubiquitous, on-demand network access to a shared pool of flexibly reconfigurable sources. The CyberGuarder is designed to address the key security issues faced by the conventional green cloud computing scenarios. The advantage of virtual-based cloud computing provides with the development of energy efficient, highly scalable network software applications (NetApp) by way of providing maximum utility of available resources. CyberGuarder is integrated into internet-oriented virtual computing infrastructure that creates a virtual machine resource management towards resource utilization. To permit the public auditability and data dynamic, a distinctive paradigm that brings the issues related to storage security in cloud poses many new security challenges. Moreover, as the data processing in cloud is distributed, the major hindrance in cloud is the accountability, where the users fears of losing control of their own data. This in turn results in distributed accountability becoming a significant barrier to the wide adoption of cloud services. At the same time, in order to overcome the problem of e-waste with integrating the old and mid-range processors with modern processors, the care regarding the resource efficiency is less. CyberGuarder has laid the foundation for providing solutions in demonstrating its important security assurance role towards the security operation. The Cloud Service Provider (SCP) is one of the important storage pools that helps with users to store their data and provides with the resources to maintain the client data. The optimal resource allocation technique in the green cloud computing provides with the utilization of two types of resources namely, processing capability and bandwidth which are being assigned simultaneously over a period of time. In this paper, various schemes for virtual computing are discussed in detail.